Tributaç\~ao do capital no Brasil e no mundo - Sérgio Wulff Gobetti (Instituto de Pesquisa Econômica Aplicada (IPEA), 2018)
– This paper aims to subsidize the current debate on tax reform, showing how the theoretical assumptions that supported the current model of income taxation in Brazil are undergoing a significant international revision, both as a consequence of the increasing inequality and the maturation of the theory of optimal taxation. This review indicates that both the progressivity and the taxation of capital income can be made compatible in a neoclassical framework that seeks to balance the search for equity and economic efficiency. In this sense, it is concluded that at least the exemption of excess return of capital (in the form of the total exemption of distributed dividends, as in Brazil) should be removed from the Brazilian tax system, suggesting the Nordic dual income tax as a reference for a proposed reform.
Keywords: A14; B20; D63; H21; H24; 330; theory of optimal taxation; dual income tax; dividends